Structure and Corrosion Resistance of Aluminum Coating with Choline Chloride Ionic Liquid on the Surface of AZ80Ti Magnesium Alloy for Construction - ZHANG Zhao-fang, LI Kui, ZHANG Lei-shun (Cailiao Baohu, 2021)
With selecting urea and choline chloride to form a new kind of ionic liquid, the electrodeposition process of Al was carried out on AZ80Ti magnesium alloy as the matrix.Subsequently, the microstructure of the deposited aluminum layer and corrosion resistance in 3.5% NaCl solution were researched.Results showed that the β microstructure of the aluminized matrix surface disappeared completely and formed some blocky structures.When the plating time was increased, the initial lamellar structure gradually grew into a granular structure, and different particles spread around to form a coating composed of particles and lamellar structure.After aluminized, the magnesium alloy obtained a higher self-corrosion potential and showed stronger corrosion resistance.After 3 h of electroplating, the optimal protection performance of aluminum coating could be obtained.Moreover, the rougher corrosion surface was formed on the initial magnesium alloy after the corrosion test, on which there were lot of corrosive collapsed products.After 3 h of electrodeposition, the surface structure with the coexistence of particles and lamella was formed, and the degree of corrosion damage reached the minimum, which formed a relatively dense lamellar structure.